The Effect of Rondo Games Training on Passing Accuracy in Football Games - Puji Wibowo; Nurhidayat, Nurhidayat (Java Mutiara Media, 2024)
The background to this research is based on the passing ability of SSB Rajawali Semarang players which is lacking and still needs to be improved as well as variations in training to improve passing techniques and the lack of passing accuracy. The aim of this research was to determine the effect of rondo games training on passing accuracy. This research is an experiment with quantitative methods and uses a